Remnant cholesterol and all-cause mortality risk: findings from the National Health and Nutrition Examination Survey, 2003-2015 - Bai, Muhan; Liao, Jiangquan; Wang, Yan; Liang, Mengqi; Wang, Chuan; Zhang, Jie; Shao, Mingjing (Frontiers in Endocrinology, 2024)
Aims: Cholesterol carried in triglyceride-rich lipoproteins, also called remnant cholesterol, is increasingly acknowledged as an important causal risk factor for atherosclerosis. Elevated remnant cholesterol, marked by elevated plasma triglycerides, is associated causally with an increased risk of atherosclerotic cardiovascular disease. However, the association with all-cause mortality and causespecific mortality is inconclusive. This study aimed to test the hypothesis that remnant cholesterol levels and plasma triglycerides are associated with increased all-cause mortality and mortality from cardiovascular disease, cancer, and other causes. Methods and results: Using a contemporary population-based cohort, 7,962 individuals from the National Health and Nutrition Examination Survey (NHANES) aged over 40 years at baseline in 2003-2015 were included. During up to 109.2 (± 1.44) months of follow-up, 1,323 individuals died: 385 individuals died from cardiovascular disease, 290 from cancer, 80 from cerebrovascular disease, and 568 from other causes.Compared with the middle tertile remnant cholesterol level, multivariable-adjusted mortality hazard ratios were 1.20 (95% confidence interval 1.02-1.40) for all-cause mortality. For the highest tertile remnant cholesterol level, multivariable-adjusted mortality hazard ratios were 1.21 (95% confidence interval 1.05,1.40). Our conclusions remained stable in subgroup analyses. Exploratory analysis of the cause of death subcategories showed corresponding hazard ratios of 1.25 (1.13-1.38) for Noncardiovascular and Non-cerebrovascular Death for lower remnant cholesterol individuals, 1.47 (1.01-2.15) for cancer death for lower remnant cholesterol (RC) individuals, and 1.80 (1.36-2.38) for cancer death for higher RC individuals.RC levels were associated with U-shaped all-cause mortality. RC was associated with mortality from non-cardiovascular, non-cerebrovascular, and cancer, but not from cardiovascular causes. This novel finding should be confirmed in other cohorts.